Improving Consistency and Accuracy of Neonatal Amplitude-Integrated Electroencephalography - Tsoi, Kathleen; Yam, Karen K. M.; Cheung, Hon M.; Ma, Terence P.Y.; So, King W.; Fung, Eva L.W.; Lam, Hugh S. (American Journal of Perinatology, 2021)
Objective This study aimed to improve the utilization of amplitude-integrated electroencephalography (aEEG) in a neonatal unit by improving aEEG documentation, aEEG knowledge, and pattern recognition ability of neonatal staff.Methods A quality improvement (QI) program comprising the two Plan-Do-Study-Act (PDSA) cycles was conducted in a level-3 neonatal intensive care unit. The first cycle was focused on improving aEEG documentation with the primary outcome indicator being compliance with aEEG documentation. The second cycle was focused on aEEG interpretation in a health care professional education program with the outcome indicators being accuracy of seizure identification on aEEG and change in conventional EEGs (cEEG) performed. Other outcome indicators included accuracy in identification of background pattern, sleep–wake cycles and artifacts. Process indicators included improvement in aEEG-related knowledge.Results First PDSA cycle includes lectures on aEEG interpretation, a bedside key, and documentation form. Second PDSA cycle includes online aEEG education pack and detailed aEEG guideline. There was a significant improvement in aEEG documentation after the implementation of both PDSA cycles. Seven of the 46 patients (15.2%) had isolated electrographic seizures which would not have been identified in the pre-aEEG monitoring era. There was an increase in the number of patients with cEEGs done but a steady decrease in number of cEEGs per patient.Conclusion With the successful application of standardized QI methods, improvements in outcome indicators, such as correct aEEG pattern recognition and improved coverage of at risk infants with cEEGs, were observed. Our QI measures were associated with improvement in aEEG pattern recognition.Key Points
Keywords: amplitude-integrated electroencephalography; neonate; quality improvement